Integrating CBS and WBS in Construction Projects by Using Data Analytics - Mik Wanul Khosiin; Wei-Chih Wang; Indradi Wijatmiko (Nusantara Science and Technology Proceedings)
In Indonesia, project databases are not well managed, covering hundreds or thousands of cost items and work items from construction projects. This condition becomes more complex when operators are required to integrate between CBS and WBS, which requires extra effort to perform detailed, rush, and accurate grouping. This study attempts to demonstrate the role of data science in managing CBS and WBS through the code system method in the pivot table. The analysis process requires four stages, step 1. data preparation, step 2. item relationship, step 3. code system analysis, and step 4. validation and evaluation. The results showed that the codes applied including A1001-A1003 have CBS and WBS derivatives in a systematic and well-structured manner so that automatically the calculation of the quantity and cost that accompanies each of these items obtains accurate results. This article is expected to provide options for field practitioners to perform data management to be efficient and productive for the continuity of construction projects going forward.